PERKEMBANGAN POPULASI KUTU PERISAI AULACASPIS TEGALENSIS ZEHNTNER (HOMOPTERA: DIASPIDIDAE) DAN PENGARUH TINGKAT SERANGANNYA TERHADAP PENURUNAN HASIL TEBU DI PT GUNUNG MADU PLANTATIONS, LAMPUNG TENGAH - Sunaryo dan Rosma Hasibuan . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2003)
Population development of a scale insect Aulacaspis tegalensis Zehntner (Homoptera: Diaspididae) and effect of its infestation on sugarcane yield loss in PT Gunung Madu Plantations, Central Lampung. Sugarcane scale insect, Aulacaspis tegalensis, is a new major pest of sugarcane in PT Gunung Madu Plantations (GMP). A survey was conducted at the experimental station of the Research and Development Division of PT GMP to investigate the population growth of the pest and effects of their infestation on sugarcane production. The first study indicated that the population of the pest started to grow when the host plants were at the age of 8 months and reached a peak (300 individuals/stem) on mature sugarcane plants (11 month old). A low population of the pest at younger sugarcane plants might be due to the fact that during their first seven months of growth, sugarcane plants had no stem or even if they had, the leaf sheaths were still closedly intact to the stem, while the scale insects could live and survive optimally at the internodes under the leaf sheaths. The second study showed that the first pest outbreak occurred in 2000 which covered 162.27 ha of sugarcane fields. In the year of 2001, the infested area increased significantly (up to 1157.93 ha). In addition, the effect of the scale insect infestation caused an enormous yield loss. The losses could be expressed as the reductions in: stem weight, pol (polarisation, sucrose content), brix (total soluble solids), and sugar contents.